High Altitude Rangelands Invasion by Non-Palatable Plant Species in the Perception of Yak Herders (Journal of Agriculture and Environment, 2022)
The biological and socio-ecological dimensions of alpine rangelands degradation by invasive species have been considered in a field survey conducted in two yaks (Bos grunniens) rearing areas i.e., Langtang National Park (LNP) and Kanchanjunga Conservation Area (KCA). Data were collected by herder’s interview using the well-prepared and pretested set of questionnaires (60), followed by a focus group discussion (FGD) and key informants survey (KIS) each five at each site by following a set of checklists.  There was a common perception about the invasive species among the herders in the study sites. The Rumex nepalensis was the most invasive species reported (75% of the respondents) at altitudes up to 3000 m in the KCA, while it was additionally with Eupatorium adenophorum (60%) in the LNP, while the Lyonia and Juniperus were the common invasive species in both sites. Altogether, twelve plant species were reported as invasive and non-palatable species from various botanical groups were indifferent to the changes made by invasive species in rangelands soil characteristics but gave well insight into the declining productivity of grasslands and herbage productivity and quality. Herders established bush clearance and slash and burn agriculture in rangelands as traditional adaptation measures to control the invasive species. Mapping of risk zones of invasive and alien species in the alpine rangelands is necessary across the alpine rangelands of Nepal and a long-term monitoring framework is desirable to confirm the herder's information on invasive alpine species of Nepalese Himalayas.